The Queer Outside in Law: Recognising LGBTIQ People in the United Kingdom - Raj, Senthorun Sunil; Dunne, Peter (Palgrave Socio-Legal Studies, 2021)
Chapter 1: Queering Outside the (Legal) Box: LGBTIQ People in the United Kingdom -- PART I: Colonising, Protecting, and Punishing Queer Outsidersin Law -- Chapter 2: Queer Legacies of Colonialism -- Chapter 3: Death Zones, Comfort Zones: Queering the Refugee Question -- Chapter 4: The DSSH model and the Voice of the Silenced:AderonkeApata: The Queer Refugee: I am a lesbian -- Chapter 5: Vulnerable and Threatening: varieties of exclusion for incarcerated Queer prisoners -- PART II: Queering the Outsides of Legal Gender and Sex -- Chapter 6: Genders that don’t matter: Non-binary people and the Gender Recognition Act 2004 -- Chapter 7: Queering the Queer/Non-Queer Binary: Problematizing the “I” in LGBTI+ -- Chapter 8: The Best Place on the Planet to be Trans? Transgender Equality and Legal Consciousness in Scotland -- Chapter 9: Coming Inside and/or Playing Outside: The (Legal) Futures of LGBTIQ Rights in the United Kingdom.